2016
DOI: 10.1159/000448140
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound Pattern Is Normal during the Last Gestational Weeks: An Observational Pilot Study

Abstract: Background/Aims: The normal lung ultrasound (US) pattern during a regular pregnancy has not been evaluated extensively in the current literature. Pregnancy-related changes in the respiratory tract affect maternal predisposition to several respiratory complications; consequently, it is important to differentiate between a physiologic pattern during pregnancy and a pathologic lung pattern, due to respiratory failure. The goal of our study was to assess the normal US lung pattern in women without known comorbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 33 publications
4
30
1
4
Order By: Relevance
“…We detected no abnormalities in the physical examination, vital parameters or laboratory test results of patients with common B‐lines and an interstitial syndrome pattern on LUS. In our study an interstitial syndrome pattern was not associated with older‐aged, obese, or multiparous women, as suggested in the literature . Our findings may influence the interpretation of LUS images in laboring patients showing deterioration resulting in B‐lines LUS pattern.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…We detected no abnormalities in the physical examination, vital parameters or laboratory test results of patients with common B‐lines and an interstitial syndrome pattern on LUS. In our study an interstitial syndrome pattern was not associated with older‐aged, obese, or multiparous women, as suggested in the literature . Our findings may influence the interpretation of LUS images in laboring patients showing deterioration resulting in B‐lines LUS pattern.…”
Section: Discussionsupporting
confidence: 84%
“…Arbeid et al used the same 8‐point LUS assessment protocol and reported the presence of only A‐lines in 75% of nonlaboring pregnant patients . In our study, only 3 of 24 women in labor had only A‐lines on LUS either before or after delivery.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations